Role of erythrocytes in short‐term rewarming kidney perfusion after cold storage. Issue 6 (2nd January 2019) - Minor, Thomas; von Horn, Charlotte; Paul, Andreas
Abstract: Short term normothermic reconditioning by machine perfusion after cold storage has shown beneficial effects in renal transplantation models. Systematic investigations concerning the inclusion of washed erythrocytes as oxygen carriers are lacking in this context. Porcine kidneys were subjected to 20 h of static cold storage. Prior to reperfusion, grafts were put on a machine for 2 h of oxygenated (95% O2 ; 5% CO2 ) rewarming perfusion. In one group ( n  = 6) washed erythrocytes were added to the perfusate after temperature has reached 20°C; the other group ( n  = 6) was run without additives. Control kidneys ( n  = 6) were immediately reperfused without treatment. Upon reperfusion in vitro, a more than twofold improvement of renal clearance of creatinine, urinary protein loss, fractional excretion of sodium, efficiency of oxygen utilization (TNa/VO2 ) and a significant reduction of innate immune activation (HMGB1, tenascin C, expression of TLR4) was seen after machine perfusion, compared with the controls. However, no advantage could be obtained by the addition of erythrocytes and inner cortical tissue pO2 always remained above normal values during cell‐free machine perfusion. Our data strongly argue in favor of a rewarming perfusion of cold stored donor kidneys but do not substantiate an indication for adding oxygen carriers in this particular setting.